Argentina : Economic Developments; February 27, 2014. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2016)
This report presents IMF staff analysis based on publicly available information through end- January 2014. Following its 2002 financial crisis, Argentina experienced a strong economic recovery, helped by an expansionary policy stance, an undervalued exchange rate, high and rising international prices for its key exports (soy, corn), and lower debt service payments. However, in 2013, balance-of-payments pressures intensified amid continuing high inflation. Economic growth recovered in 2013, though weakened sharply in the second half of the year. Inflation remained high. Financial deepening increased somewhat and financial stability was preserved despite the high inflation and growing external imbalances. Fiscal policy in 2013 was more expansionary than in the previous year.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet